DEVELOPMENT OF MEDIA COMPETENCE THROUGH AN INTEGRATIVE APPROACH USING ARTIFICIAL INTELLIGENCE TOOLS (IN ENGLISH LANGUAGE CLASSES) - Tog’ayeva Muattar Bahodir qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This article explores the development of media competence among students through an integrative approach that incorporates artificial intelligence (AI) tools in English language classes. In the context of rapid digital transformation, media competence has become a critical skill, enabling learners to effectively access, analyze, evaluate, and create media content. The study examines how AI-powered tools—such as chatbots, automated writing assistants, and multimedia generators—can enhance language learning while simultaneously fostering media literacy. The research employs a mixed-method approach involving experimental teaching, surveys, and performance analysis.  The  findings  indicate  that  integrating  AI  tools  into  English  language instruction  significantly  improves  students’  critical  thinking,  digital  literacy,  and communicative competence. The article concludes with pedagogical recommendations for  educators  aiming  to  implement  AI-based  integrative  strategies  in  language classrooms.